2009
DOI: 10.1021/jp900246p
|View full text |Cite
|
Sign up to set email alerts
|

Residual Solvent Effects on Free Volume and Performance of Fluorinated Polyimide Membranes: A Molecular Simulation Study

Abstract: In this study, molecular simulation techniques were used to investigate the residual solvent effects on the free volume and performance of 6FDA-mPDA polyimide (PI) membranes. A molecular dynamics (MD) simulation was used to analyze how the residual solvent in the 6FDA-mPDA PI membrane affects the fluctuation and flexibility of the polymer segment and the free volume. The gas sorption in the membrane was analyzed by a Monte Carlo (MC) technique. The energy analysis of the MD simulation indicates that the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…It has been shown that polyimide films contain small amounts of residual solvent. [38][39][40] In this study, the imidization solvent, NMP, became yellow under the reaction conditions [ Fig. 1(d)].…”
Section: Optical Properties Of Polyimidesmentioning
confidence: 86%
“…It has been shown that polyimide films contain small amounts of residual solvent. [38][39][40] In this study, the imidization solvent, NMP, became yellow under the reaction conditions [ Fig. 1(d)].…”
Section: Optical Properties Of Polyimidesmentioning
confidence: 86%
“…The strong effect of membrane preparation parameters on the performance of the membranes has been studied by several researchers, often in relation with amount of residual solvent [19][20][21][22][23][24][25]. As speculated elsewhere [16,[20][21][22][23][24], imprints of solvent molecules left in the polymer chain structure formation throughout the preparation period affect the transport properties severely.…”
Section: Introductionmentioning
confidence: 99%
“…Often, permeability is well correlated with fractional free volume (FFV), as suggested from theoretical considerations, which is used as a tool for structure characterization. It is well known that the presence of CF 3 groups produces larger and more effective free volume elements for gas diffusion, and also supplies more sites for gas sorption, both factors contributing to higher permeability . However, the permeability data obtained for PI‐2 and PI‐5 demonstrate that this general trend may be upset, and the effectiveness of CF 3 groups in increasing permeability may be reduced if the chain stiffness is significantly decreased as indicated by the lower T g value of PI‐5 .…”
Section: Resultsmentioning
confidence: 97%